PERBANDINGAN HUKUM PENGAMBILALIHAN PERUSAHAAN MENURUT HUKUM PASAR MODAL INDONESIA DAN AMERIKA SERIKAT - Wicaksono, Raden Mas Try Ananto Djoko (LITIGASI, 2021)
This article discusses capital market law in gathering expertise in Indonesia and the United States (US) as well as legal protection for stakeholders related to the process of gaining expertise. In this study a method use a comparative approach that is descriptive in nature. The results of the research conducted show that there are some similarities in the implementation of tenders between Indonesia and the US, but there are some differences, such as the procedures for protecting the stakeholders related to the process of making expertise. Keywords: Capital Market Law, Company Expertise Taking, Public Company, United States Law, Business Law.